What determines supportive behaviors following bereavement? A systematic review and call to action - Logan, Emma; Thornton, Jennifer; Breen, Lauren (Routledge, 2018)
Very few factors that impact the grieving process can be modified after the fact to the extent that social support can. However, social support has received limited research attention, resulting in little conceptual understanding of the mechanisms behind perceptions of, and intentions to support, grieving persons. This systematic review aimed to explore bereaved, decedent, and respondent-related determinants of the provision of social support. The review yielded 42 studies impacted by various methodological and sampling limitations. This review poses a call to the field for more rigorous study of social support determinants to better assist the bereaved and their natural supporters.